Penerapan Metode Pembelajaran Team Games Tournament (TGT) dengan Aplikasi Kahoot untuk Melatih Penguasaan Kosakata Bahasa Jerman Siswa Kelas XI SMA Negeri 6 Malang - Ismi Ninda Annisa; Sawitri Retnantiti (Singular: Journal of Pedagogical Language, Literature, and Cultural Studies, 2025)
This research aims to describe the application of Team Games Tournament (TGT) method with Kahoot application to train the mastery of German vocabulary of 11th grade students of SMA Negeri 6 Malang and to describe students' responses to the application of the method. The research used descriptive qualitative approach with observation instrument, Kahoot quiz, and student questionnaire. The results showed that TGT method based on Kahoot application made students participate and motivated in learning German vocabulary. Students are more active, enthusiastic, and helped in remembering vocabulary. The findings of this study are time constraints and differences in understanding sentence structure during learning with TGT and Kahoot.This TGT method with Kahoot application is proven to be applicable in learning German language interactively.